2017
DOI: 10.3390/molecules22071053
|View full text |Cite
|
Sign up to set email alerts
|

Eu@C72: Computed Comparable Populations of Two Non-IPR Isomers

Abstract: Relative concentrations of six isomeric Eu@C72—one based on the IPR C72 cage (i.e., obeying the isolated-pentagon rule, IPR), two cages with a pentagon–pentagon junction (symmetries C2 and C2v), a cage with one heptagon, a cage with two heptagons, and a cage with two pentagon–pentagon fusions—are DFT computed using the Gibbs energy in a broad temperature interval. It is shown that the two non-IPR isomers with one pentagon–pentagon junction prevail at any relevant temperature and exhibit comparable populations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 58 publications
2
19
0
2
Order By: Relevance
“…22. The Mulliken-charge choice is supported 32 by the fact that it is in good agreement with the available observed charges 33 for metallofullerenes. However, unless there are charges deduced from observations for a class of clusterfullerenes, it cannot really be decided which particular charge denition is the best 34 for the class.…”
Section: Resultssupporting
confidence: 74%
“…22. The Mulliken-charge choice is supported 32 by the fact that it is in good agreement with the available observed charges 33 for metallofullerenes. However, unless there are charges deduced from observations for a class of clusterfullerenes, it cannot really be decided which particular charge denition is the best 34 for the class.…”
Section: Resultssupporting
confidence: 74%
“…The approximative orbital-energy analysis [34] performed at the B3LYP/3-21G∼SDD level also rather supports the four-electron transfer. In order to clarify the charge transfer further, some observed information would still be needed like that available for simple metallofullerenes [35,36].…”
Section: Resultsmentioning
confidence: 99%
“…[62] Similarly,in2017 Slanina et al computed six isomers of Eu@C 72 and concluded that the two DFP-containing non-IPR cage isomers,namely, C 2v (11188)-C 72 and C 2 (10612)-C 72 , were favored for Eu@C 72 . [63] It was then intriguing to discover whether DFPs could be stabilized in the form of amonometallofullerene by atrivalent metal, for which af ormal three-electron transfer from the encapsulated metal to the carbon cage occurs.I n2 006, Akasaka and co-workers successfully captured La@C 72 as the first trivalent metal based non-IPR monometallofullerene in the form of its dichlorophenyl derivative La@C 72 (C 6 H 3 Cl 2 ), which was synthesized by extracting raw soot with 1,2,4trichlorobenzene.T he molecular structure of La@C 72 -(C 6 H 3 Cl 2 )w as elucidated unambiguously by single-crystal X-ray diffraction, which revealed it had a C 2 (10612)-C 72 cage with ap air of DFPs (Figure 2a). [15] It was observed that the encapsulated La atom was situated near the fused pentagons so as to enable its coordination with the fused pentagon, and the exohedral dichlorophenyl group was attached to one of the carbon atoms within the fused pentagon through the high singly occupied molecular orbital (SOMO) spin density and the high p-orbital axis vector (POAV )p yramidalization angle.…”
Section: Stabilization Of Double Fused Pentagons (Dfps)mentioning
confidence: 99%